Evaluation of neurodevelopmental symptoms in 10 cases of neonatal ichthyosis and sclerosing cholangitis syndrome. Issue 4 (18th March 2022) - Salik, Deborah; Hadj‐Rabia, Smail; Hohl, Daniel; Vahidnezhad, Hassan; Youssefian, Leila; Rakosi, Adèle; Dangoisse, Chantal; Marangoni, Martina; Vilain, Catheline; Smits, Guillaume
Abstract: Neonatal ichthyosis and sclerosing cholangitis (NISCH) syndrome is an extremely rare entity with only 19 patients described in the literature. We report an extended family with the disorder and investigate the association of neurodevelopmental symptoms. Patients with CLDN1  mutations, and specifically « the Moroccan» c.200_201delTT deletion, may be an increased risk for neurodevelopmental symptoms such as learning disabilities, mental retardation, and language delay.